Pengembangan Media Pembelajaran Berbasis Aplikasi Articulate Storyline 3 pada Pembelajaran Pendidikan Pancasila di Kelas V SD Wilayah I Lubuk Kilangan Kota Padang - Sitorus, Hiskia; Wulandari, Fikhen Tri; Anita, Yesi; Zuryanty, Zuryanty (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop a valid, practical, and effective Articulate Storyline 3 application-based learning media to be used in the learning process in elementary schools. The type of research used is Research and Development (R&D) with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The data collected includes the validity, practicality, and effectiveness of the media. The results of validation by experts showed a validity rate of 100% from subject matter experts, 97.7% from media experts, and 84.4% from linguists, with an average of 94.03% in the "very valid" category. The practicality test by the teacher showed a result of 90% at SDN 15 Koto Lalang, 93.33% at SDN 10 Bandar Buat, and 93.33% at SDN 14 Koto Lalang, with an average of 92.22% (categorized as 'very practical'). Meanwhile, the practicality test by the students showed results of 94.33%, 96.16%, and 95.13%, with an average of 94.33% (categorized as 'very practical'). The effectiveness test through N-Gain calculation showed a significant improvement in learning outcomes, namely 0.66 (categorized as 'sufficiently effective') at SDN 15 Koto Lalang, as well as 0.77 (categorized as 'effective') at SDN 10 Bandar Buat and SDN 14 Koto Lalang. Thus, the developed learning media is declared valid, practical, and effective in supporting the learning process at the elementary school level.